The new secrets of style : your complete guide to dressing your best every day - Alfano, Jennifer (InStyle, 2009)
Updated with hundreds of new photos and ideas, this resource shows how to develop true personal style that is always uncomplicated and flattering. The guide is the perfect personal fashion companion.